Characterization of the complete chloroplast genome of Ginkgo biloba L. (Ginkgoaceae), an endangered species endemic to China. Issue 2 (3rd July 2019) - Jiao, Peng; Qi, Zhuo; Jiang, Zhenzhong; Qu, Jing; Guan, Shuyan
Abstract: Ginkgo biloba L. is the oldest relict plant among the gymnosperms, left after the quaternary glacial movement. There are few living G. biloba and few old trees over a hundred years old. It is currently on the International Union for Conservation of Nature (IUCN) red list of threatened species. In this study, we first assembled the complete chloroplast (cp) genome of G. biloba L. by Illumina paired-end reads data. The whole genome was 156, 988 bp, consisting of a pair of inverted repeats of 34, 056 bp, large and small single copy regions of 56, 819 and 22, 763 bp in length, respectively. The cp genome contained 131 genes, including 84 protein-coding genes, 31 trRNA genes and 5 rRNA genes. The overall GC content of the whole genome was 39.6%. A neighbour-joining phylogenetic analysis demonstrated a close relationship between G. biloba L. and Cycas revoluta .